The AJ521 antibody detects the human CD1b protein by western blot - Cino, Aurélie; Sassi, Ali; Bulla, Monica; Arsimoles, David; Pirek, Cyril; D’Esposito, Alessia; Haraj, Mustafa; Gueorguiev, Boris; Domingos, Elisa; Guilhen, Cyril (Antibody Reports, 2020)
The AJ521 antibody detects the human CD1b protein by western blot.